Parques eólicos e conflitos ambientais: luta e resistência ao projeto Complexo Eólico Baleia em Itapipoca/CE - Viana, Lígia Alves (2016)
The development model based in Brazil is part of a scenario characterized by the advance of world capitalism and the technological demands to intensify the availability of energy is a fundamental element to guarantee production and expansion of the economic logic of capital accumulation. The investment in large infrastructure and energy projects in the country is the scenario adopted by the national policy as a measure to ensure the development and expansion of production, mainly of commodities. However, energy projects such as wind farms occupy vast areas and cause a series of impacts on the populations where they settle. In this sense, this study seeks to analyze the processes of environmental conflicts and (injustices) occasioned by the project to implement the Baleia Wind Complex in the surroundings of the Maceió Settlement, located in Itapipoca / CE. For that, a trajectory of research based on participant research was designed from the perspective of counter-hegemonic science, in the construction of a study in dialogue with the dynamism of reality so that it becomes a product of demand and sharing between knowledge, with a view to collectively building participatory processes of knowledge production. The global geopolitical constitution reveals a scenario of structural crisis of the hegemonic mode of production and the questions about the contradictions of the logic of accumulation of capital as the only logic of life on the planet are deepened. In this sense, the outputs pointed to a system that is based on contradictions reveal a worsening of its destructive essence. The subjects involved in this process of shared knowledge construction demonstrate that there is an infinite number of alternative possibilities to human existence that point to a logic of conception of the world in which the social, cultural, epistemic and environmental aspects are indissociated, revealing a differentiated worldview and outside of the logic of capital, marked by the heterogeneity of knowledge and practices of reproduction of life.